Enabling Scientific Workforce for African Research-Intensive Universities (Journal of Science, Technology and Innovation Policy, 2021)
There is a strong desire for research development in Africa. Nigeria and South Africa remain the largest producers of scientific research publications in West Africa and Africa respectively. However, this does not amount that there is a strong research output from the regions. African institutions suffer from chronic underinvestment and poor implementation of research as development agenda. This study evaluates research productivity in Africa based on scientific contributions and innovative research published between 2008 - 2019 in Scopus database and compares them with selected top ten countries across the world. This selections are considered top most countries Africa countries has research collaboration with, the comparison was done using Clarivate Analytics Incites and sourced data from Scimago Institutional Ranking database. Findings revealed that Africa universities are not performing to expectations. This led to the formulation of two main research questions based on how African governments are connecting with capable scientific workforce across the selected countries, what are the research funding and training mechanism put in places, and how do the region appreciates self-funding researchers who are becoming assets in the foreign countries and “brain drain” to the African region. The study gives input that will enable Africa institutions to rise among top ranking research universities in the world and presents how government and institutions in Africa can produce quality scientific researchers.
Keywords: Research Development, Scientific Research and Innovation, Scientific Publications, Nigeria Research Index, Research and innovation output